The Effect of Some Postharvest Applications on Storage Performance of Autumn Giant Plum Cultivar - Feyza Nur Dursun; Erdinc Bal (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effect of postharvest salicylic acid (2 mM), oxalic acid (5 mM), putrescine (2 mM) and calcium (4% CaCl2) applications on storage performance of Autumn Giant plum fruit were investigated. After applications, plum fruits were placed in modified atmosphere packaging (MAP) and stored for 40 days at 85-90% relative humidity conditions at 0.5±0.5°C. In order to determine the fruit quality characteristics after treatments, weight loss, soluble solids content, titratable acidity, fruit firmness, ascorbic acid, total flavonoids, total phenolics and total antioxidant content analysis were performed at 10 days’ intervals. According to the results, the effect of applications on weight loss was not significant. The maximum decrease in flesh firmness, titratable acid and ascorbic acid content during storage was determined in control fruits. Although fluctuations in the form of increase or decrease in biochemical compounds were generally observed, decreases occurred according to harvest value at the end of storage period. Considering all measurements and evaluations, it was determined that application of salicylic acid and putrescine had a more positive effect on preservation of fruit quality properties and biochemical content of Autumn Giant plum cultivar during storage than other applications.